System Communication In Multicentre World (What Luhmann Systems Theory Declares) - Šubrt, Jirí; Pincová, Barbora (Communication Today, 2025)
The paper deals with the problems of communication as they are analyzed in the framework of the systems theory of Niklas Luhmann. For Luhmann, modern society is functionally differentiated society, i.e. it is composed of heterogeneous but equal parts which are relatively independent in nature and which are denoted as partial so-cial systems, i.e. sub-systems. The condition necessary for the existence of social systems is communication, and to ensure this, the systems create social mechanisms – the media- whose purpose is to stabilize the communica-tion processes. In social development, there have been differentiated media sub-systems communications, which Luhmann regards as symbolically generalized media. Luhmann’s analysis presents contemporary society as a whole differentiated into functionally dependent yet autonomous sub-systems that constitute neighbouring worlds for each other. On the basis of its observations of society, each sub-system generates its own image and thus instead of a centrally conceived world a multicentre world emerges.